PERANCANGAN APLIKASI EVALUASI KINERJA PEGAWAI DENGAN MENGGUNAKAN METODE GROUP ALGORITMA PROGRAMING - Lahmudin Sipahutar; Yan yang Thanri (INFOSYS (INFORMATION SYSTEM) JOURNAL, 2021)
The company PT.Surya agroloika Reksa is a company engaged in oil palm plantations by owning private gardens in Riau province, and has 2000 employees with their respective positions. Human resources within an organization are very important to support the progress and quality of the company in achieving its goals. The foreman position at PT Surya Agrolika Reksa has shortcomings in determining the foreman's position. So far, the selection of foremen has only been based on job rankings.Applications designed with the Groub method programming algorithm will summarize several points needed in determining the foreman's position. The application will calculate these points, so the calculation process is faster and doesn't take a long time.The data collection technique used is observation by directly observing the work process carried out to obtain a clear picture of the object under study. Interviewing is conducting a direct dialogue with the authorities in providing information on the required data and studying literature by searching for literature. supporting libraries.